2021
DOI: 10.3390/ijerph18105419
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Lifetime Suicide Attempts among Mexican Adolescents, over the Past 12 Years

Abstract: Objective. To compare the occurrence of suicide attempts across nationally representative samples of the Mexican adolescent population over the past 12 years, and to analyze its association with sociodemographic, lifestyle and mental-health indicators. Methodology. Data were drawn from the 2006, 2012 and 2018 National Health and Nutrition Surveys (n = 25,056; 21,509; and 17,925 adolescents, respectively). Estimates were based on standardized measurements. Results. The estimated lifetime prevalence rates of sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(28 reference statements)
0
4
0
2
Order By: Relevance
“…( Dubé et al, 2021 , Rockstroh et al, 2021 , Romero-Martínez et al, 2019 , Romero-Martínez et al, 2021 , Valdez-Santiago et al, 2021 , Xiong et al, 2020 , Gutiérrez-García et al, 2017 , Hermosillo-de la Torre et al, 2021 , Instituto Nacional de Estadística Geografía e Informática defunciones por suicidio por entidad federativa y grupos de edad según sexo 2010-2019 2021 , Instituto Nacional de Estadística Geografía e Informática. Encuesta Nacional de Ocupación y Empleo 2021 )…”
Section: Uncited Referencesunclassified
“…( Dubé et al, 2021 , Rockstroh et al, 2021 , Romero-Martínez et al, 2019 , Romero-Martínez et al, 2021 , Valdez-Santiago et al, 2021 , Xiong et al, 2020 , Gutiérrez-García et al, 2017 , Hermosillo-de la Torre et al, 2021 , Instituto Nacional de Estadística Geografía e Informática defunciones por suicidio por entidad federativa y grupos de edad según sexo 2010-2019 2021 , Instituto Nacional de Estadística Geografía e Informática. Encuesta Nacional de Ocupación y Empleo 2021 )…”
Section: Uncited Referencesunclassified
“…Canadian data also showed increased self-harm in adolescents aged 12–18 years ( n = 809) which was associated with personal and societal COVID-19-related stress (Robillard et al, 2021). Studies from the United Kingdom and Mexico did not report any change in rates of suicide and self-harm during the pandemic (Polek et al, 2020; Valdez Santiago et al, 2021).…”
Section: Resultsmentioning
confidence: 97%
“…We located five community-based surveys from Korea, Mexico, the United States, the United Kingdom, and Canada (Kim et al, 2021; Murata et al, 2021; Polek et al, 2020; Robillard et al, 2021; Valdez-Santiago et al, 2021). Kim et al (2021) reported reduced suicidal thoughts, plans, and attempts in Korean 12–18-year-olds during the pandemic with an OR 0.77, 95% CI (0.73–0.80) for suicidal thoughts; an OR 0.88, 95% CI (0.81–0.96) for suicide planning; and an OR 0.64, 95% CI (0.58–0.70) for suicide attempts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque en México las conductas suicidas se han estudiado ampliamente desde un punto de vista epidemiológico [14], pocos estudios se han centrado en conocer el rol de los servicios de salud en el abordaje del suicidio y, en particular, sobre los obstáculos que enfrenta el personal de salud para la atención de las conductas suicidas [15]. Por lo tanto, el objetivo de este estudio fue identificar las barreras que existen para la atención de las conductas suicidas, desde la perspectiva del personal de salud mental del primer nivel de atención de la Ciudad de México.…”
Section: Introductionunclassified